2021
DOI: 10.51847/f5z7stooft
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Colorectal Cancer in Saudi Arabia: Cross-Sectional Study

Abstract: Colorectal Cancer (CRC) is a global medical challenge. In the KSA, it is 1 st cancer among males, 3 rd among females, with a death rate of 8.3%. The main purpose of CRC screening is to detect cancer in early stage where cure can be achieved. So, this study aimed at evaluating the public awareness of CRC and determining the preferred methods to conduct the awareness of this concept. A cross-sectional study was performed in Jeddah, KSA, in 2019. Data collection was done using an online questionnaire that was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The sample size was calculated according to the following formula: N = (Z1-α/2) 2 P (1-P)/d2 = (1.96)2 × 0.52 × (0.48)/(0.5)2 = 383.4 ~ 384. Here, (Z1−α/2) is the standard normal variate at 5% type 1 error (1.96); (P) is the expected proportion of awareness in Saudi Arabia (52%) [ 12 ]; and (d) is the absolute error (0.05). The sample was completed at 412.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated according to the following formula: N = (Z1-α/2) 2 P (1-P)/d2 = (1.96)2 × 0.52 × (0.48)/(0.5)2 = 383.4 ~ 384. Here, (Z1−α/2) is the standard normal variate at 5% type 1 error (1.96); (P) is the expected proportion of awareness in Saudi Arabia (52%) [ 12 ]; and (d) is the absolute error (0.05). The sample was completed at 412.…”
Section: Methodsmentioning
confidence: 99%
“…Al-Sharif et al, in their survey, stated that in the Asir region of Saudi Arabia, approximately one-third of respondents correctly identified the function of both the colon and rectum; 71.6% knew what a colon or rectum is; around 22% were aware of the precise incidence of CRC; and 23% correctly recognized the timing of CRC testing [11]. In their study of more than 4000 people from everywhere in Saudi Arabia, Alkhayyat et al discovered that 44% of respondents believed that an important indicator linked to CRC was unexplained weight loss and approximately 61% were unfamiliar with CRC screening methods [12]. Alotaibi et al conducted another national survey in Saudi Arabia and found that of the 521 participants, around half had a low level of awareness of the symptoms and risk factors associated with CRC [13].…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that females are more aware that red or processed meat is a risk factor for CRC. In addition, older participants knew that eating red or processed meat increases the risk of developing CRC compared to younger adults [ 17 ]. Azzeh et al did a case-control study for 137 patients with colon and/or rectal cancer in the Mecca region of Saudi Arabia to investigate the risks and protective benefits of dietary factors affecting CRC [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRC is the second most common cancer among Saudi population. 1033 is the number of cases that was reported in Saudi Arabia in 2010 which represents only 10.4% of the newly diagnosed patients [9]. There were 1908 cases accounting for 12.2% of all newly diagnosed cases in the year 2018 reported by Saudi cancer incidence report.…”
Section: Introductionmentioning
confidence: 99%